Diving: Simple laws of biomechanics - Stefanon, F.
After some diving-specifis definitions autor explains: - THE CENTRE OF GRAVITY OF A DIVER, - CREATING ROTATION , - OVERBALANCING (LEAN) , - MOMENTUM TRANSFER (JERK) , - MOMENTUM = MASS times VELOCITY, - ECCENTRIC LEG THRUST (HIPS BENT), - ECCENTRIC BOARD THRUST.